The Mandate of the World Russian People’s Council and the Russian Political Imagination: Scripture, Politics and War - Alar Kilp; Jerry G. Pankhurst (Religions)
The Mandate of the XXV World Russian People’s Council of 27 March 2024 framed the Russian war of aggression against Ukraine as a “holy war”. This paper presents an in-depth textual analysis of the Mandate followed by an extended thematic and contextual analysis. The findings indicate that the Mandate’s mainstream discourses of eschatological–apocalyptic holy war and katechon state were not previously expressed at the level of official church leadership. They contribute to the ideological escalation of the Russian confrontation with Ukraine and the West around declared traditional values and the holy mission of the Russian people, while the involvement of Orthodoxy in the Russian ‘holy war’ narrative is neither exclusive of other religious referents nor of disbelief in ecclesial doctrine. The main referent of the Self (and correspondingly, of the sacred) is the (Russian) ‘nation’ or ‘people’, for which ‘spiritual’ and ‘civilizational’ are comprehensive religious markers of cultural identity. While two religious adversaries of the Russian geopolitical agenda of Ukraine—the Ecumenical Patriarchate and Ukrainian Orthodoxy—are not directly mentioned in the Mandate, it nevertheless attempts to re-formulate an Orthodox ‘just war’ theory, intensifies antagonistic inter-Orthodox relations in the Russia–Ukraine dimension and strengthens the resolve of the Russian Orthodox Church (ROC) and the Russian Federation to retain Ukraine’s Orthodox Church as an exclusively Russian space.